A driver node selection strategy for minimizing the control energy in complex networks 1. Issue 1 (July 2017) - Lindmark, Gustav; Altafini, Claudio
Abstract: This paper deals with the problem of controlling linear complex networks in an efficient way, i.e., with limited control energy. A general principle is provided, based on the eigenvalues of the network. It is shown numerically that the cost of controlling a network grows with the (absolute value of the) real part of the eigenvalues of the adjacency matrix. Constructive rules for driver node selection are also provided, based on the (weighted) topology of the network. In particular, we show that the key to have an energetically efficient driver node placement strategy is to use the skewness of the outdegree versus indegree distributions of the network, a topological property not associated before to controllability.